Goalkeeper decision making in football: the effect of uncertainty of actual game situation - Lin, Terence Qisheng (Nanyang Technological University, 2022)
Purpose: The purpose of this study was to examine and compare the effects of uncertainty on the movement responses and visual search strategy between novice and expert goalkeepers. Methods: 2 expert goalkeepers from the Singapore Premier League participated in this study. Participants were equipped with an eye tracker and performed 20 saving trials of different attacking scenarios in certain or uncertain conditions. Kinovea and BeGaze were used to analyse the footage for goalkeepers’ position and displacement within the goal, and duration of gaze spent on each area of interest. Data collected from novices were then compared with this data set and analysed. Results: No visual data were analysed due to invalid data. No significant differences (p > 0.05) were found in movement responses between novices and experts. However, it was found that movement responses of experts were consistent throughout conditions and attacking scenarios, whereas the movement responses of novices were varied between attacking scenarios, with movements being more reserved in uncertain conditions. Conclusion: The certainty of an outcome had no significant effects on the movement responses between expertise levels and decision-making ability of the goalkeepers.